Optimization of interfacial polymerization thin film composite membrane for separation of xylose from glucose - Mah, Kah Hong (2016)
Most hydrolysis studies on biomass in Malaysia produce high amount of xylose and glucose compared to other monosaccharides. These monosaccharides are important ingredients often needed in pure fraction in food and pharmaceutical industries. Chromatography and commercial nanofiltration membrane were able to separate xylose from glucose. However, few treatment steps on biomass hydrolysate were needed because most biomass hydrolysate are acidic. Acidity reduces the performance of these separation technology by inhibiting chromatography resins and fouling of membrane. Thin film composite membrane developed via interfacial polymerization using triethanolamine and trimesoyl chloride as monomers allows separation at low pH to occur without damaging its performance. Currently, almost none has attempted to separate xylose from glucose using self-made thin-film composite membrane that is specially tailored for biomass hydrolysate. The aim of this present study was to produce optimized thin-film composite nanofiltration membrane for separation of xylose from glucose using triethanolamine and trimesoyl chloride as monomers on polyethersulfone membrane via interfacial polymerization using a series of experimental design. Success of thin layer formation was probed by attenuated total reflectance-Fourier transform infrared spectroscopy, and prepared membranes were characterized by field emission scanning electron microscope, contact angle and pure water permeability. Separation performance of thin-film composite membranes are affected by several factors during formation of thin upper layer. Series of experimental designs were applied to screen and optimize the different interfacial polymerization factors studied. In screening, 25-1 fractional factorial design were used to find significant factors affecting xylose separation factor, which are reaction time and curing process. Also, the responses in screening were fitted with a multiple linear regression equation and obtained a high correlation (R2 = 0.9998) between the experimental data and model data. Then central composite design was used to identify the optimum interfacial polymerization conditions for the highest xylose separation factor. The response was fitted with the second-order polynomial equation with R2 of 0.92, implying a high correlation between the observed and predicted values. The optimum interfacial polymerization conditions were determined to be reaction time of 45.25 minutes, curing time of 15.53 minutes, and curing temperature of 58.4 ℃. At optimum conditions, the xylose separation factor was found to be 1.334 ±0.007. The developed model in this study is adequate for predicting xylose separation factor under different interfacial polymerization conditions within the range used. This study will provide valuable guideline to develop membrane that specially tailored for xylose separation from glucose as alternative to the cost intensive chromatographic processes in use.